PENGARUH BAURAN PROMOSI TERHADAP BRAND IMAGE GOJEK INDONESIA - Amalia, Rizky (Jurnal Insani, 2020)
Gojek Indonesia is a transportation service based on mobile application. Gojek is the first online transportation service in Indonesia. Originally focused on transportation service, Gojek expands the business on more than twenty kind of services which became solution for daily activity. Gojek became one of the biggest platforms of technology that serve many people at Southeast Asia. Gojek’s accomplishment is the result of promotion mix that create an excellent brand image. Based on those contexts, the formulation of a research problem is how far the promotion mix can affect the brand image of Gojek Indonesia. This research uses the concept of promotion mix and brand image. The research method is the positive paradigm with quantity approach of explanatory research. Is the user of Gojek Indonesia who become the followers of @dramaojol.id., the data collection method is surveys. The research instrument is questionnaires that created from Google Form. The data analysis method is the simple regression analysis. The research shows that there is a significant influence of the promotion mix on the brand image of Gojek Indonesia but the effect is sufficient. A promotion strategy is needed that is more attractive and maximizes the use of the dimensions of sales promotion and public relations as an integral part of promotion in order to build a stronger brand image.